Libras as a subject in the Language Course of the Federal Institute of Education, Science, and Technology from Ceará: a comparative analysis of the course program: (Research, Society and Development, 2020)
This paper aims to analyze the course program from the Libras' subjects and Introduction to Libras study, of the graduation in Language Courses from the Federal Institute of Education, Science, and Technology from Ceará (IFCE), that works at the campus from Baturité, Camocim, Crateús, Tauá, Tianguá, and Umirim. It is an exploratory documental study that uses a qualitative approach. The data collection was made on the institution's official website, where the Courses' Pedagogical Projects (PPC) can be found. It was assumed a comparative analysis in thematic nuclei according to Bonitatibus (1989) and Minayo et.al. (2015).  It was observed the majority of the subjects of Linguistic Foundations and Communication in Libras in the course programs, to the detriment of the Foundations of Deaf Education and Deaf Education in the Inclusive Perspective. New systematics researches that analyze the course programs of these subjects in all graduations from the institution are suggested in this study, to confirm or refute the hypothesis raised here and to understand the IFCE curriculum in its entirety.